EDUCATIONAL TECHNOLOGY OF CONTEXTUAL LEARNING, WHICH ARE IMPLEMENTED BY MEANS OF SPECIAL DISCIPLINES - Чупахін, Сергій Анатолійович (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article deals with contradictions between the content of teaching and the requirements which are put forward for future professionals by the customers. In order to eliminate these inconsistencies there is a need for contextual learning. It is of greater importance at the final stage of formation of professional competence of future specialists while studying special subjects. Based on the analysis, the author grounds educational technologies, which should be applied in the contextual approach in the educational process: projects, games, excursions, exhibitions training company and their comprehensive use. This will enable to form the professional competence of future specialists providing complete conception of customer’s enterprises and the processes which occur there